2008
DOI: 10.1097/dad.0b013e31818118f7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of B-Cell Clonality Using the BIOMED-2 PCR Method Effectively Distinguishes Cutaneous B-Cell Lymphoma From Benign Lymphoid Infiltrates

Abstract: Primary cutaneous B-cell lymphomas (CBCL) are a diverse group of lymphomas that are limited to the skin at the time of diagnosis. Recently, standardized polymerase chain reaction protocols for immunoglobulin (Ig) rearrangement in nodal malignancies using the BIOMED-2 method have been studied extensively. However, reports of investigations of Ig clonality in CBCL using the BIOMED-2 method have been scant. We hypothesized that clonality detection in CBCL with the BIOMED-2 method could effectively distinguish mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 39 publications
1
49
1
3
Order By: Relevance
“…If PCBCL with indolent behavior is suspected and benign lymphocytic infiltrates cannot be excluded by clinical evaluation, histology, and immunohistochemistry, BIOMED-2 can be a valuable differentiating tool. 22 Morales et al 22 detected monoclonality in 22 of 26 cases of PCBCL with indolent behavior. We consistently detected monoclonality in 10 of 11 cases of PCBCL with indolent behavior.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…If PCBCL with indolent behavior is suspected and benign lymphocytic infiltrates cannot be excluded by clinical evaluation, histology, and immunohistochemistry, BIOMED-2 can be a valuable differentiating tool. 22 Morales et al 22 detected monoclonality in 22 of 26 cases of PCBCL with indolent behavior. We consistently detected monoclonality in 10 of 11 cases of PCBCL with indolent behavior.…”
Section: Discussionmentioning
confidence: 97%
“…15,20,21 Recently, it was shown that BIOMED-2 can differentiate between benign lymphoid infiltrates in the skin and PCFCL/PCMZL. 22 However, sensitivity differs in the subgroups of PCBCL and in the studies. 22,23 Furthermore, it has not been determined if molecular staging might be possible for PCLBCL, LT, which has a more aggressive course.…”
Section: T He World Health Organizationeeuropeanmentioning
confidence: 98%
See 1 more Smart Citation
“…Morales et al [99] tackle the difficult problem of separating reactive (n=23) form malignant (n=26) B-cell proliferations in the skin, using the Biomed set of primers. In patients with a lymphoma, a clone was detected in 85% of the samples, and in only 4% of the reactive infiltrate was the data very promising.…”
Section: Ancilliary Techniquesmentioning
confidence: 99%
“…29,30 Polymerase Chain Reaction Analysis Polymerase chain reaction (PCR) was performed with an IGH assay using FR2 and FR3 primers (Invivoscribe Technologies, San Diego, CA), according to the manufacturer's protocol. 31 The PCR products were analyzed by capillary electrophoresis on an ABI PRISM 3100 Genetic Analyzer (Applied Biosystems, Foster City, CA).…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%